PENGARUH PROFITABILITAS DAN MODAL INTELEKTUAL TERHADAP NILAI PERUSAHAAN - Andhieka, Krisnayana Tio; Retnani, Endang Dwi (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2017)
ABSTRACTThis research is meant to examine whether there is an influence of profitability and intellectual capital to the firm values which are listed in Indonesia Stock Exchange. Profitability has been measured by using the ROA (Return on Asset) ratio, intellectual capital has been measured by using VAIC (Value Added Intellectual Coefficient) ratio, and the firm value has been measured by using Tobinâs Q ratio. The data is the secondary data in the form of annual report of every consumer goods companies which are listed in Indonesia Stock Exchange during 3 (three) year periods in 2013-2015. The samples have been obtained by using purposive sampling and these samples have met the sample selection criteria. 23 consumer goods companies have been selected as samples. The hypothesis test of this research has been conducted by using F significance test and t statistic. The result of this research shows that profitability has been measured by using ROA give positive influence to the firm value. Meanwhile other variables i.e. intellectual model which is measured by using VAIC does not give any influence to the firm value.Keywords: Profitability, intelectual capital, firm value.